Implementing Online Ordering Systems for Small Culinary Businesses: A Case Study of Nasi Cia - Anugrah, Charisma Christ; Istiono, Wirawan (Jurnal Tekno Kompak, 2025)
In the era of culinary industry growth and digital transformation, the challenges for startups like Nasi Cia in managing rice orders are increasingly complex. In the environment of SMA Xaverius 1, the surge in visitors often results in problems in managing orders efficiently. The manual system used today proved insufficient to handle the increasing order load. The problem of long queues also affects the customer experience and can lead to losing potential customers. Lack of sales data management is also a problem that must be solved. To overcome these problems, an online ordering system was built and designed using the extreme programming method. With this application, Nasi Cia switches to a more effective ordering system with the aim of improving flexibility, responsiveness, and service quality, as well as reducing dependence on expensive food delivery applications such as Gojek and Grab. The results and conclusions of this research show that this application has been successfully built with the extreme programming development method. This online ordering application can be well received as evidenced by 91.4% of users strongly agree